Overview of four Agaricus subrufescens strains used in the last 15 years in Brazil and other countries and current potential materials for the future - Zied, Diego C. [UNESP]; Vieira Junior, Wagner G. [UNESP]; Soares, Douglas M. M.; Stevani, Cassius V.; Dias, Eustáquio S.; Iossi, Matheus R. [UNESP]; Pardo-Giménez, Arturo (Springer Nature, 2021)
The mushroom Agaricus subrufescens has been synonymous with Agaricus blazei and Agaricus brasiliensis during the last decades, and there has been much discussion with regard to the origin, distribution, and nomenclature of this mushroom. Therefore, we conducted a genetic and morphological characterization of the mycelium and mushroom of four commercial strains currently cultivated in Brazil (ABL CS7, ABL 18/01, ABL 98/11, and ABL 16/01) together with an assessment of their agronomic behavior and compared these results with those published in works using other strains during the last 15 years. All the A. subrufescens strains characterized here are phylogenetically related to the Americas/Europe specimens, bearing an internal transcribed spacer region of type A (ABL 16/01) or both types A and B (ABL 18/01, ABL 98/11, and ABL CS7). We did not find any correlation between the morphological characteristics of the mycelial colonies and the agronomic behavior of the strains. Strains ABL 98/11 and ABL 16/01 produced the best yields and morphological characteristics for the mushrooms, indicating their high weight, which enhances the commercialization of the mushroom and justifies their longstanding commercial use over the last 15 years.
Keywords: Agaricus blazei; Agaricus brasiliensis; Genetic characterization; Screening of mushroom quality; Yield